Reporting Outcomes and Outcome Measures in Open Rhinoplasty: A Systematic Review. (3rd May 2019) - Hassan, Yusuf; Leveille, Cameron F; Gallo, Lucas; Santos, Jenny; Thoma, Achilleas; McRae, Mark H; McRae, Matthew C
Abstract: Background: Comparative studies have shown little statistical difference in outcomes following rhinoplasty, demonstrating near equivalent results across all surgical techniques. Cross-study comparisons of these trials are difficult because variation in outcome reporting prevents statistical pooling and analysis. Objectives: The authors sought to identify all outcomes and outcome measures used to evaluate postoperative results in rhinoplasty. Methods: An extensive computerized database search of MEDLINE and EMBASE was performed; all trials involving n ≥ 20 patients, aged 18 years and older undergoing a primary, open rhinoplasty procedure, were included for review. Results: Of the 3235 citations initially screened, 72 studies met the stated inclusion criteria. A total of 53 unique outcomes and 55 postoperative outcome measures were identified. Outcomes were divided into 6 unique domains: objective signs, subjective symptom severity, physical function related to activities of daily living, patient satisfaction, surgeon satisfaction, and quality of life. The identified outcome measures consisted of 5 nasal-specific, author-reported instruments; 5 nasal specific, patient-reported instruments; 5 patient-reported, generic instruments; and 40 author-generated instruments. Of the outcome measures identified, the Rhinoplasty Outcomes Evaluation, Sino-Nasal Outcome Test-22, and FACE-Q were the only instruments to demonstrate adequate validity, reliability, and responsiveness to change in patients who underwent a rhinoplasty procedure. Conclusions: There is heterogeneity in the outcomes and outcome measures employed to assess postsurgical outcomes following rhinoplasty. A standardized core outcome set is urgently needed to make it possible for future investigators to compare results of various techniques in rhinoplasty surgery. Level of Evidence: 2: